Dendritic polylysine co-delivery of paclitaxel and siAXL enhances the sensitivity of triple-negative breast cancer chemotherapy - Wan, Xiaofeng; Chen, Chuanrong; Zhan, Jianmin; Ye, Shuke; Li, Runsheng; Shen, Ming (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Drug resistance is common in triple-negative breast cancer (TNBC) therapy. To identify a method to overcome chemotherapy resistance in TNBC cells, a siRNA targeting the AXL gene (siAXL), which can overcome drug resistance, was used in this study. A nanodelivery system was constructed to codeliver siAXL and paclitaxel (PTX). Methods: A biodegradable and tumour microenvironment (TME)-sensitive mPEG-coated dendritic polylysine material (PDPLL) was synthesized. This material was used to construct single-molecule nanoparticles to codeliver PTX and siAXL. The drug encapsulation and morphological properties of the nanoparticles (NPs) were characterized. The sensitivity of the NPs to the TME was evaluated in vitro with a dialysis method. The tumour-targeting effect of the PDPLL NPs was evaluated by fluorescence imaging and drug distribution evaluation in vivo. The ability to overcome drug resistance was evaluated using PTX resistant 4T1 cells (4T1/PTX cells) in both in vitro and in vivo models. Results: PDPLL NPs had a particle size of 49.6±5.9 nm and a zeta potential of 7.87±0.68 mV. The PTX DL% was 2.59%. The siAXL DL was 2.5 mg PDPLL: 10 nmol siAXL. The release of PTX showed sustained release performance. The release of siAXL showed sensitivity for the TME. The NPs were stable in the plasma. The NPs promoted cell uptake by PTX-resistant 4T1 cells (4T1/PTX) and promoted tumour targeting and permeability in vivo. siAXL enhanced the toxicity and apoptosis efficiency of PTX in 4T1/PTX cells, as well as the cycle arrest efficiency caused by PTX. The NPs improved the above effects. In mouse 4T1/PTX orthotopic tumours, the NPs enhanced the sensitization of PTX to siAXL. Conclusion: The PDPLL NP codelivery system possesses good encapsulating potential not only for PTX but also for siRNA. It can enhance the tumour-targeting effect and overcome the drug resistance of 4T1/PTX both in vitro and in vivo. This system is a potential delivery system for RNAs.